Simulation-based training for breastfeeding competency development in midwifery practice: a concept analysis - N. R., Deepa; R., Vidyashri; Abirami, M.; Yadav, Anupama; T., Smita; Munusamy, Gomathi; R., Gandhimathi; B., Ariyalakshmi; R., Dhanya; P. K., Krishna Prabha; Balamurugan; Umar, Mohammed (International Journal of Contemporary Pediatrics, 2026)
Breastfeeding competency is a core professional requirement in midwifery practice and significantly influences maternal and neonatal health outcomes. Despite global recommendations advocating exclusive breastfeeding, gaps persist in practical skill preparation and clinical confidence among midwifery students. Simulation-based training has emerged as an innovative educational strategy; however, its conceptual meaning within breastfeeding competency development remains inadequately defined. This study aimed to clarify the concept of simulation-based training for breastfeeding competency development in midwifery practice using Walker and Avant’s eight-step concept analysis methodology. A systematic literature search was conducted across PubMed, Scopus, CINAHL, and Web of Science databases for studies published between 2000 and 2025. Sixty-four relevant articles were included in the final synthesis. Five defining attributes were identified: structured experiential learning, simulated clinical environment, competency-based evaluation, facilitated reflective debriefing, and clinical transferability. Antecedents included curricular gaps, technological advancement, maternal–infant health priorities, and ethical considerations in clinical training. Consequences encompassed improved psychomotor skills, enhanced clinical confidence, strengthened breastfeeding support practices, and potential improvement in maternal satisfaction and breastfeeding outcomes. An operational definition was developed to guide curriculum design, research standardization, and policy development. Concept clarification supports the integration of simulation-based strategies into competency-based midwifery education to enhance breastfeeding support quality and maternal–newborn health outcomes.